Forced internal migration in the Kharkiv region: structural-dynamic and regional features - Нємець, Людмила; Гусєва, Наталія; Логвинова, Марина; Кандиба, Юрій; Ключко, Людмила (Human Geography Journal, 2018)
The article deals with the structural-dynamic and regional analysis of the IDPs of the Kharkiv region. It was determined that in terms of the number of IDPs, the proportion of IDPs in the all-Ukrainian value and the number of IDPs per 1000 local residents, Kharkiv region ranks 4th in Ukraine. Among the possible factors that influenced and influence the choice of the migrants of the Kharkiv region as a region for their residence are the following: territorial proximity to temporarily uncontrolled districts of Donetsk and Luhansk regions; similar to Donbass industrial specialization, which expands the employment opportunities of forced migrants; high level of urbanization; sociocultural and political characteristics of the local population; relatively high level of support for IDPs by regional authorities and local governments, as well as some others.It is reasonable that the official number of IDPs in the region is somewhat exaggerated due to the so-called. "Pension tourism" and will be real only after the cancellation of the peg payment of pensions to the status of IDPs. It was noted that since February 2016 there has been a tendency to reduce the number of IDPs in the region, which is caused by the depopulation of the population; the return of forced migrants to temporarily uncontrolled areas of Donbass and the Autonomous Republic of Crimea; the cancellation of IDP certificates as a result of the work of the departments of social protection of the population to streamline the registration of IDPs; migration abroad; the integration of the most successful immigrants into local communities; unwillingness to confirm the status of IDPs due to bureaucratic barriers and periodic inspections and some other reasons.It was revealed that in the age structure of IDPs in the region, pensioners dominate, in the sex – women, and in the educational structure – people with higher education.